2020
DOI: 10.25046/aj050315
|View full text |Cite
|
Sign up to set email alerts
|

University Students Result Analysis and Prediction System by Decision Tree Algorithm

Abstract: The main assets of universities are students. The performance of students plays a vital role in producing excellent graduate students who will be the future viable leader and manpower in charge of a country's financial and societal progress. The purpose of this research is to develop a "University Students Result Analysis and Prediction System" that can help the students to predict their results and to identify their lacking so that they can put concentration to overcome these lacking and get better outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the field of educational data mining, many studies have explored the use of decision tree algorithms for predicting student performance. One such study, conducted by the author of [13], compared three different decision tree algorithms and found that J48 was the most effective for classifying and predicting student actions. The study also noted that the decision tree graphs' structure was influenced by the number of input attributes and the end class attributes.…”
Section: Related Workmentioning
confidence: 99%
“…In the field of educational data mining, many studies have explored the use of decision tree algorithms for predicting student performance. One such study, conducted by the author of [13], compared three different decision tree algorithms and found that J48 was the most effective for classifying and predicting student actions. The study also noted that the decision tree graphs' structure was influenced by the number of input attributes and the end class attributes.…”
Section: Related Workmentioning
confidence: 99%
“…However, it should be noted that this study employed a more limited dataset, resulting in decreased accuracy. In [13], researchers employed three distinct decision tree algorithms-Hoeffding Tree, J48, and REPTree-to predict university results and aid students in improving their performance by identifying areas of weakness. The dataset for university students encompassed a wide range of information, including assignment marks, attendance, class test marks, extracurricular activities, gender, tuition frequency, programming skills, and preceding semester Grade Point Averages (GPA).…”
Section: Related Workmentioning
confidence: 99%
“…The purpose of the proposed project was to create a more efficient framework that significantly improved student performance. Reference [12] used WEKA (Waikato Environment for Information Analysis) as a testing tool for data classification. Working on this paper was very difficult with tree size, entropy, and other factors.…”
Section: Related Workmentioning
confidence: 99%